Can we beat the “buy-and-hold” strategy? Analysis on European and American securitized real estate indices - Hui, Eddie C. M.; Yam, Sheung-Chi Phillip (International Journal of Strategic Property Management, 2014)
The aim of this paper is to use the Shiryaev-Zhou index to examine the performances of securitized real estate indices of four countries: US, UK, Canada and Germany. The result reveals that the Shiryaev-Zhou index is a leading indicator and can act as a predictor on certain securitized real estate indices. Furthermore, our results show that the trading strategy we constructed according to the Shiryaev-Zhou index generally outperforms the “buy-and-hold” strategy under the assumption of no transaction costs. The stronger the predictive power of the Shiryaev-Zhou index is, the larger extent our trading strategy beats the “buy-and-hold” strategy. This is useful in strategic property management that property practitioners can follow our strategy to trade real estate stocks/funds in order to increase their profits. First Publish Online: 21 Mar 2014